\(=\left(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{6}\right)+\left(\dfrac{2}{5}-\dfrac{4}{35}+\dfrac{5}{7}\right)-\dfrac{1}{41}=-\dfrac{1}{41}\)
\(\dfrac{1}{2}-\dfrac{-2}{5}+\dfrac{1}{3}+\dfrac{5}{7}-\dfrac{-1}{6}+\dfrac{-4}{35}-\dfrac{1}{41}\)
\(=\dfrac{1}{2}+\dfrac{2}{5}+\dfrac{1}{3}+\dfrac{5}{7}+\dfrac{1}{6}+\dfrac{-4}{35}+\dfrac{-1}{41}\)
\(=\left(\dfrac{1}{2}+\dfrac{1}{3}+\dfrac{1}{6}\right)+\left(\dfrac{2}{5}+\dfrac{5}{7}+\dfrac{-4}{35}\right)+\dfrac{-1}{41}\)
\(=1+1+\dfrac{-1}{41}\)
\(=2+\dfrac{-1}{41}=\dfrac{81}{41}\)